Sustainable thin shell analysis on structural foundation subjected to seismic loads - Azizah Abdul Nassir; Yee Hooi Min; Arthit Petchsasithon; Syahrul Fithry Senin (My University, 2023)
Abstract Shell structures are recognized for their exceptional performance in withstanding compression forces, often utilized as roof components. However, Southeast Asia experiences significant annual losses due to floods, with inadequate structural mitigation despite high population concentrations in seismic risk areas. Previous research explored thin shell structures as elevated foundations to mitigate flood effects on buildings. Unfortunately, the proposed shell design exceeded the material’s strength limit of 40N/mm 2 , limiting its feasibility. To address this, our study proposes a modified thin shell with a 600mm thickness. Finite Element analysis using LUSAS software evaluated the new design’s structural behavior under dynamic loads from earthquakes and flood-induced waves. Results demonstrate a substantial reduction of up to 99% in equivalent stress compared to the previous model [ Model P ]. The revised model [ Model C ] proves feasible in withstanding intense building loads, ensuring maximum stress remains below the concrete material’s strength limit. Implementation of these findings offers valuable structural mitigation, reducing flood impacts and enhancing both structural resilience and human safety.
Keywords: Limiting; Resilience; Foundation (evidence); Structural Analysis and Optimization